TINJAUAN BEBAN LENTUR DAN REMBESAN AIR PADA GENTENG DENGAN BAHAN TAMBAH LIMBAH SERBUK KACA - Cintia Pratiwi; Kusno Adi Sambowo; Supardi Supardi (Matriks Teknik Sipil, 2014)
Glass powder has considerable volume in wastes and has not thoroughly been utilized. Therefore, the waste glass powders can maximally be exploitedby utilizing them as the aggregates of roof tile manufacture. The objective of this research is to investigate the effect of waste glass powders asthe aggregates of the roof tile manufacture on the flexural load and water absorption. The test specimens consisted of four main groups based on thepercentage of waste glass powders, namely: 0%, 5%, 10%, and 15% of the dry weight of clay. Each group consisted of 10 test specimens, andtherefore the total number of the specimens was 40. Flexural load was tested by using bending testing machine, and the water absorption was testedby using the pvc pipe with the diameter of ¾'' and the length of 6 cm. The result of the specimen testing shows that the values of the averageflexural load with percentage of the waste glass powder supplementation of 0%, 5%, 10%, and 15% were 50 kg, 62 kg, 72 kg, and 63 kg respectively.the increasing supplementation of the waste glass powder was increasing the value of flexural load but after passing the optimum limitflexural load will decrease. The result of the regression analysis shows that the optimum flexural load was obtained in the waste glass powdersupplementation of 9.817% with the value of flexural load of 69.469 kg. All of the roof tiles with or without the waste glass powder supplementationwere included in the roof tile classification of Class IV of the standards of PUBI 1982. In addition, the result of the water absorption testingshows that the increasing supplementation of the waste glass powder was reducing the percentage of the water absorption. Therefore, the supplementationof the waste glass powder was improving the quality of the roof tiles.